2022
DOI: 10.2196/35000
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Applications in Medicine During the COVID-19 Pandemic: Systematic Review

Abstract: Background Virtual reality can play an important role during the COVID-19 pandemic in the health care sector. This technology has the potential to supplement the traditional in-hospital medical training and treatment, and may increase access to training and therapies in various health care settings. Objective This systematic review aimed to describe the literature on health care–targeted virtual reality applications during the COVID-19 crisis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 238 publications
0
6
0
Order By: Relevance
“…Some medical disciplines have adapted by leveraging novel technologies, from virtual reality and digital simulations to podcasts and social media. [18][19][20][21] Similarly, it will be incumbent on AM practitioners and educations to consider digital possibilities in AM curriculum redevelopment. It is likely the COVID-19 pandemic will continue to transform AM education by driving innovation and propelling training…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some medical disciplines have adapted by leveraging novel technologies, from virtual reality and digital simulations to podcasts and social media. [18][19][20][21] Similarly, it will be incumbent on AM practitioners and educations to consider digital possibilities in AM curriculum redevelopment. It is likely the COVID-19 pandemic will continue to transform AM education by driving innovation and propelling training…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is imperative to augment educational platforms and build resilience within training settings. Some medical disciplines have adapted by leveraging novel technologies, from virtual reality and digital simulations to podcasts and social media 18–21 . Similarly, it will be incumbent on AM practitioners and educations to consider digital possibilities in AM curriculum redevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst to date there has been little urology specific research into how these can further education and training, there has been benefit shown in other fields of medicine. One recent review revealed that its relatively modern usage through the COVID pandemic was well tolerated by users and associated with a higher learning speed when compared to standard classroom teaching [ 28 ].…”
Section: Ai and Vrmentioning
confidence: 99%
“…This accessibility has helped thousands of PWDs, albeit with various degrees. Moreover, the adoption of virtual reality and serious games in AT domain is gaining momentum worldwide, particularly after the paradigm shift brought about by the COVID-19 pandemic which necessitated searching for alternatives that cope with staying at home needs [8]. Nevertheless, stronger research evidence is required to determine the clinical-and cost-effectiveness of these AT devices for types and degrees of disabilities and elderly conditions.…”
Section: Main Textmentioning
confidence: 99%